Assessment of the level of influence of oil exporting countries’ organizations on the world oil market - A. A. Laznik; T. S. Gordeeva (Вестник университета)
Oil is one of the signiﬁcant energy resources for the majority of the world’s states, so many of them monitor and analyze the price of black gold. Currently, there are such organizations of oil exporting countries as OPEC and OPEC+, which for a long time continue to inﬂuence not only the world market of this energy resource but also the events taking place in the economic and political spheres of the world. These organizations’ actions have a direct impact on market conditions, policy making, oil price, and the volume of its supply on the market in world trade. The collective responsibility of the member countries for a signiﬁcant portion of global oil production makes the decisions and actions of OPEC and OPEC+ extremely important for the global oil industry and the economy as a whole. All the above-mentioned points to the relevance of the topic of the study, the objectives of which are to analyze the history of the emergence of the oil exporting countries’ organizations, the dynamics of their development during the history of their existence, as well as to assess the degree of their inﬂuence on the oil industry and the global economy as a whole.